The life story from age 26 to 32: Rank‐order stability and mean‐level change. Issue 5 (2nd November 2017) - Sengsavang, Sonia; Pratt, Michael W.; Alisat, Susan; Sadler, Pamela
Abstract: Objective: In this longitudinal, mixed‐methods project, the primary focus was to examine the rank‐order stability and mean‐level change in the life story during the period of emerging adulthood to young adulthood, while also investigating how the transition to parenthood may impact the life story. Method: Seventy‐two participants described three key life story scenes at age 26 and again at 32 (28% attrition from age 26 to 32). The narratives were coded for a range of features, including motivational themes (agency, communion), affective themes (emotional tone), an integrative meaning theme (coherent positive resolution), and a structural property (narrative complexity). Results: Overall, there was moderate temporal stability and mean‐level increase in several features of narrative identity over this key period. Positive changes in communion levels and overall emotional tone of life story scenes were especially evident for new parents at age 32. Conclusions: These longitudinal results suggested that adopting new social roles, in this case becoming a parent, predicted how the life story was expressed, just as they seemed to influence other levels of personality, such as traits, following the social investment principle.